[Group marching near Dexter Lawn] (1995)
The march participants are walking on University Drive sidewalk with Dexter lawn on their left. A fence is raised up along the sidewalk, just past where the lawn ends. One student is wearing a yellow and white shirt and is riding a bicycle in the opposite direction of the march.